Combined Aerobic and Strength Training Improves Dynamic Stability and can Prevent against Static Stability Decline in Postmenopausal Women: A Randomized Clinical Trial - Marques, Ana Claudia Fortaleza; Rossi, Fabrício Eduardo; Neves, Lucas Melo; Diniz, Tiego Aparecido; Messias, Iracimara de Anchieta; Barela, José A.; Horak, Fay B.; Júnior, Ismael Forte Freitas (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To analyze the effect of combined training (CT) in postural control and gait parameters in postmenopausal women.Methods A parallel-group, randomized, control study was conducted with 16 weeks of combined training (n = 16) versus a non-training control group (n = 12) in postmenopausal women (aged 59.3 ± 8.0). Pre and postintervention assessments included postural control (using an AMTI force platform – Advanced Mechanical Technology, Inc., Watertown, MA, USA) and gait impairments (using baropodometry). In addition, the upper limb strength and abdominal tests, as well as aerobic capacity, assessed functional indicators.Results The CT intervention in postmenopausal women resulted in improved gait (stride length (p = 0.006); speed (p = 0.013); double support time (p = 0.045); and improved postural control (displacement area of postural sway in a normal base of support with eyes open (p = 0.006). Combined training increased functional indicators (abdominal - p = 0.031; aerobic capacity - p = 0.002).Conclusion In conclusion, combined aerobic plus strength training effectively improved gait and balance control in older women. The postmenopausal women from the CT group walked faster and with bigger steps after the intervention than the control group. In addition, they presented decreased postural sway in standing and decreased the percentage of double support time while walking, which means improved static and dynamic balance control and functional indicators.
Keywords: physical exercise; menopause; balance; concurrent training; gait